Study on factors affecting separation of xylose from glucose by nanofiltration using composite membrane developed from triethanolamine (teoa) and trimethyl chloride (tmc) - Mah, Kah Hong (2014)
Xylose is an abundant raw material coexists with other sugars that can be turned into useful products, such as ethanol, xylitol and 2, 3-butanediol by microorganism such as yeasts, bacteria, and mycelial fungi. However more than 80 % of the production cost come from production of xylose solely, where recovery of xylose relied on chromatographic separation alone. Nanofiltration offers more economical solution to currently in use chromatography method, by usage of composite membrane developed from economical active monomer, triethanolamine (TEOA). In this study, factors affecting the process, pressure, concentration of total sugars in solution, and composition of monosaccharides in total sugar, were investigated using two-level factorial analysis. The experiment was perform using Amicon Milipore stirred cell (Model 8200) with constant stirring speed at 300 rpm and temperature at ambient. Membrane was prepared by conventional interfacial polymerization of TEOA and tri-methyl chloride (TMC) on polyethersulfone (PES) porous membrane. The glucose and xylose concentration was quantified using high performance liquid chromatography (HPLC). In this study, it was found that the composition of xylose to glucose has affected the nanofiltration the most, at 63.56 %, followed by total sugar concentration at 19.52 %, pressure contributed the least at 0.033 %. An interaction between factor total sugar concentration and composition of xylose to glucose were also found to contribute 16.10 % on nanofiltration. The coefficient of determination (R2) from analysis of variance (ANOVA) study was 0.9921. In a nutshell, nanofiltration using membrane developed from TEOA and TMC as monomers on PES membrane has the ability to separate xylose from glucose. Overall in this present study it can be concluded that nanofiltration has high potential to replace currently in use chromatograhic method in xylose separation